The challenges of women leaders of business organizations in Addis Ababa, Ethiopia, in balancing work-family responsibilities. - Bahiru, Bruktawit; Mengistu, Abeba Beyene (Journal of International Women's Studies, 2018)
Women's leadership significantly contributes to building high-performing organizations. However, challenges with balancing work and family responsibilities are inhibiting them from exerting their fullest potential towards this end. This study aims at investigating the challenges women leaders in Addis Ababa face in balancing the demands of their organizations with that of their families. A sample of eight women leaders of positions from large and middle scale organizations were taken using a purposive sampling technique. In-depth interviews were used to gather information for the study, and a phenomenological qualitative study was applied to analyze the data. The study identified some organizational, societal, and individual factors that challenge women leaders in balancing their work and family responsibilities. Work overload, cultural and social norms, family responsibilities, and upbringing related behaviors of the interviewees themselves were among the major challenges in maintaining their work-family balance. This study contributes insights into work-family balance theory and practice, by presenting women leaders' voices about their work-life challenges as expressed in their own words, from their own testimonies. It indicates that much needs to be done on the part of organizations, society, family, and women themselves for women leaders to have the desired level of work-family balance.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; discours dominant; famille; inégalités; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie

Against the odds? Keeping a nontraditional division of domestic work after first parenthood in Spain. - Dominguez-Folgueras, Marta; Jurado-Guerrero, Teresa; Botía-Morillas, Carmen (Journal of Family Issues, 2018)
This article analyzes changes in the division of routine domestic work after first parenthood. We wanted to know whether and how it was possible for couples to resist the trend toward traditionalization that has been shown in the literature. To do so, we analyze semistructured interviews with 27 Spanish couples who were expecting their first child in 2011 and interviewed them again in 2013. The couples were selected from a bigger sample because of their nontraditional practices preparenthood. Our results show that 17 of them were able to maintain a nontraditional division of domestic work, whereas 10 traditionalized. In our analysis, relative resources and time availability did not sufficiently explain the changes in the division of work, but specific characteristics of the division of work before childbirth—men’s active participation, the routinization of tasks, and flexible standards—emerged as key factors to resist the trend toward more traditional arrangements. © 2017, © The Author(s) 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; division sexuelle du travail; espagne; europe; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Des luttes intimes, des luttes collectives - Seery, Annabelle (Travail invisible. Portrait d’une lutte féministe inachevée, 2018)
Keywords: 2000 à aujourd'hui; amériques; charge mentale; couple hétérosexuel; famille; inégalités hommes-femmes; maternité; militance; projet charge mentale; périodes historiques; québec; régions géographiques; thématiques; travail

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

Les cheffes d’entreprise et jeunes entrepreneures de Lomé (Togo) : des « superwomen » de la double journée de travail professionnel et domestique ? - Vampo, Charlotte (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Le Togo, pays à forte tradition commerciale, présente un taux élevé d’activité des femmes. Celles-ci sont encouragées à entreprendre et disposent librement de leurs revenus. Parallèlement, elles ont la charge quasi intégrale du travail domestique. Si la plupart d’entre elles sont cantonnées aux activités informelles, certaines cheffes d’entreprise ont réussi à se faire une place dans la capitale dans des secteurs émergents de l’économie formelle. L’enquête porte sur ces archétypes de l’émancipation féminine par le travail, qui ont fait des études supérieures et qui sont dans des associations qui promeuvent l’entrepreneuriat des femmes et leur empowerment. Objectifs : Cet article explore la manière dont elles adhèrent à la division sexuelle du travail (DST) traditionnelle. Il questionne les ressources dont elles disposent pour gérer leur quotidien entre contraintes familiales et obligations professionnelles dans le but de discuter les reconfigurations dans les rôles genrés. Méthodologie : Pour ce faire, la réflexion s’appuie sur des terrains ethnographiques réalisés à Lomé au cours des cinq dernières années. Une micro-analyse des rapports de genre est privilégiée dans le souci d’appréhender les itinéraires de réussite des entrepreneures dans une approche relationnelle. Le matériel empirique se compose d’entretiens, d’observations en entreprises et en dehors de celles-ci, de discussions informelles et d’un questionnaire sur la répartition des dépenses et des tâches au quotidien. Résultats : Les résultats indiquent que la conciliation travail professionnel-travail domestique est considérée comme un devoir de femme mariée. La principale ressource dont disposent ces femmes pour s’organiser est le transfert des charges domestiques sur d’autres femmes autant au domicile que dans l’entreprise. Conclusions : L’adhésion à la DST est déterminée par la place occupée par le mariage dans la réussite et par des enjeux de reconnaissance sociale associés au rôle reproducteur des femmes. Les cheffes d’entreprise de Lomé ne pourraient pas être les superwomen qu’elles essayent d’être sans le recours à d’autres femmes. Contribution : L’accès des femmes à des postes à fortes responsabilités ne modifie pas complètement les rôles de genre si l’on se penche spécifiquement sur la division sexuelle du travail. La reconfiguration des rapports de genre est partiellement dépendante de l’empowerment économique des femmes. Toutefois, la négociation sociale du statut de cheffe d’entreprise se fait dans la transgression des normes de genre mais surtout dans la perpétuation d’un ordre inégalitaire de genre qui accompagne paradoxalement les changements. Cet article nous invite à reconsidérer l’empowerment comme un processus socio-politique à la fois individuel et collectif.
Keywords: afrique; anthropologie; approches et analyses; conciliation famille-travail; discipline; division sexuelle du travail; droits des femmes*; famille; femmes entrepeneures; histoire et politique; projet charge mentale; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; togo; travail

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail